Prebiotic potential and metabolic benefits of Acorus gramineus rhizome-derived polysaccharides in a high-fat diet-induced obesity model - Park, Miri; Chae, Yu-Rim; Lee, Hye-Bin; Lee, Jang-Eun; Lee, Yu Ra; Hur, Jinyoung; Park, Ho-Young (Frontiers in Nutrition, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a global health issue that causes severe liver abnormalities and metabolic dysregulation, incurring substantial costs to healthcare systems. Acorus gramineus, a traditional remedy, has been studied for its anti-inflammatory and neuroprotective effects. However, its potential role in the management of metabolic disorders via its polysaccharide components remains unclear. This study aimed to investigate the effects of the A. gramineus rhizome-derived polysaccharide (AGRP) on prebiotic potential and metabolic health in a high-fat diet-induced obesity mouse model. AGRP showed prebiotic efficacy by targeting representative intestinal microorganisms and demonstrated the ability to promote butyrate production. Importantly, mice fed a high-fat diet supplemented with AGRP showed significant improvements in metabolic disease markers, including reductions in body fat and white adipose tissue mass, compared to those in controls. Additionally, serum metabolic analysis of AGRP-administered mice demonstrated positive changes in liver enzymes, lipid profile, and glucose metabolism, as well as reduced lipid accumulation and downregulation of lipogenic genes. AGRP increased the intestinal barrier function by modulating endotoxins and tight junction protein expression, demonstrating its interaction with improved intestinal health. These findings suggest that AGRP is a promising prebiotic with potential applications in the management of MASLD and related metabolic disorders.